The effect of mass irregularities of weft yarns on fabric surface protrusion. Issue 5 (3rd May 2016) - Moezzi, Meysam; Ghane, Mohammad; Shahsavari, Farid
Abstract : Fabric surface unevenness and defects are usually created by yarn irregularity and defects in weaving process. These unevenness and irregularities appear on fabric and affect various fabric properties. In order to investigate weft yarn mass irregularities on fabric surface unevenness and defects, various plain fabric samples were prepared in which they differ only in weft yarn mass irregularity. One of the effective factors on fabric surface unevenness is yarn protrusion in fabric structure. Yarn protrusion in fabric structure is influenced by yarn's physical and mechanical properties and fabric structural characteristics. In this work, relationship between mass irregularities of weft yarn and fabric surface unevenness was investigated using angular power spectrum curve, a measure of yarn protrusion in fabric structures. The results showed a high significant correlation between these two parameters.